Clinical impact of enhanced diagnosis of invasive fungal disease in high-risk haematology and stem cell transplant patients. Issue 1 (22nd December 2008) - Barnes, R A; White, P L; Bygrave, C; Evans, N; Healy, B; Kell, J
Abstract : Aims: To investigate the impact of routine use of biomarkers for diagnosing fungal infection within a care pathway on antifungal usage and clinical outcomes. Methods: A cohort of high-risk haematology and stem cell transplant patients was entered into a neutropenic care pathway in which targeted diagnostic testing replaced empiric antifungal treatment. Patients were screened twice a week by PCR and antigen testing during fever or when chronic graft versus host disease was present and were followed-up for a minimum of 1 year. Results: No excess morbidity or mortality was seen in patients in whom empiric antifungal treatment was withheld, and there were substantial savings in antifungal drug expenditure. Conclusions: The introduction of a comprehensive diagnostic surveillance strategy to exclude invasive fungal infection in high-risk patients with haematological malignancy and those undergoing transplantation can result in improvements in clinical management. There are also potential additional benefits of improved patient survival, decreased morbidity and decreased hospital stay.